A mechanistic model of lateral rail head deflection based on fastening system parameters. (October 2017) - Chen, Zhe; Andrawes, Bassem
This paper presents a mechanistic model of the rail head lateral deflection with the aim of quantifying the distribution of the lateral wheel load in a concrete sleeper rail track. The model is developed based on observations of the field experimentation and the results of a three-dimensional validated finite element model. The input parameters of the model are primarily based on the design of the fastening system and the track structure. In the developed model, the rail head lateral deflection is divided into two components which are computed separately: rail base lateral deflection and rail head rotational deflection. The model considers the possible gap between the field-side shoulder and insulator, and assumes Coulomb Law of friction for the rail base interfaces. Based on an experimental design approach, the prediction of the mechanistic model is compared with that of finite element model as well as with field data.